2018
DOI: 10.1109/jlt.2017.2782882
|View full text |Cite
|
Sign up to set email alerts
|

Optical Transmitter Based on a 1.3-μm VCSEL and a SiGe Driver Circuit for Short-Reach Applications and Beyond

Abstract: Long-wavelength vertical-cavity surface-emitting lasers (LW-VCSELs) with emission wavelength in the 1.3-µm region for intensity modulation (IM)/direct detection optical transmissions enable longer fiber reach compared to C-band VCSELs, thanks to the extremely low chromatic dispersion impact at that wavelength. A lot of effort has been recently dedicated to novel cavity designs in order to enhance LW-VCSELs' modulation bandwidth to allow higher data rates. Another approach to further improve VCSEL-based IM spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 22 publications
0
16
0
1
Order By: Relevance
“…Moreover, high relaxation-resonance frequencies, and reduced parasitic effects guarantee high-speed modulations [6]. Both O and C band devices present a current aperture of about 5 µm and an effective cavity length of 2.5 µm leading to modulation bandwidths up to 20 GHz with relative intensity noise below -140 dB/Hz [4,5]. In Fig.…”
Section: A Long Wavelength Sc-vcselsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, high relaxation-resonance frequencies, and reduced parasitic effects guarantee high-speed modulations [6]. Both O and C band devices present a current aperture of about 5 µm and an effective cavity length of 2.5 µm leading to modulation bandwidths up to 20 GHz with relative intensity noise below -140 dB/Hz [4,5]. In Fig.…”
Section: A Long Wavelength Sc-vcselsmentioning
confidence: 99%
“…In order to further increase the line rate to 50 Gb/s, a suitable solution could be the adoption of fixed wavelength short-cavity (SC) VCSELs, reliable both in O and C bands and providing modulation bandwidths up to 17 GHz [4,5]. Since chromatic dispersion (CD) is the main impairment when increasing the serial rate beyond 25 Gb/s in an IM/DD system, we evaluate the resilience of DMT modulation for fiber lengths compliant with access distances in case of single sideband (SSB) filtering using suitable simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Fiber reaches for these applications range from 100m up to 2km for intra data center links and at least 10km for inter data center links. While many proposed solutions rely on external modulation implemented in III-V or Silicon Photonics material systems [2,3], links based on directly modulated VCSELs have the potential to provide low power, low cost and low complexity solutions [4][5][6][7][8][9][10]. In [4][5][6], short wavelength multimode VCSELs were reported that achieve bitrates as high as 100Gb/s.…”
Section: Introductionmentioning
confidence: 99%
“…However, transmission in the Cband is limited by chromatic dispersion in standard single-mode fiber (SSMF) and hence O-band VCSELs are promising to achieve a higher bitrate x distance product. In [10], a directly modulated link using a 1325nm VCSEL is reported, capable of reaching 28Gb/s using NRZ over 20km and 40Gb/s over 4.5km. Link performance is limited by the bandwidth of the O-band VCSEL, which is still less compared to state of the art C-band VCSELs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation